2019
DOI: 10.1002/ffj.3514
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of three essential oils (cinnamon, manuka, and winter savory), and their synergic interaction, against Listeria monocytogenes

Abstract: Essential oils (EOs) are categorized as having antimicrobial, insecticidal, and antioxidant activities. For their antibacterial activity, EOs are widely studied as alternatives to antibiotics in human and veterinary medicines. The inhibitory and bactericidal activities of three EOs (Cinnamomum zeylanicum, Leptospermum scoparium, and Satureja montana) were determined against Listeria monocytogenes ATCC 7644. The chemical compositions of the EOs were determined through gas chromatography mass spectrometry (GC‐MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(38 reference statements)
3
7
0
Order By: Relevance
“…Furanoeudesma-1,3-diene, a particular compound with antimicrobial activity [37], was also present in high percentage in Commiphora molmol EO (33.7%). The compounds most represented in Leptospermum scoparium EO, which have demonstrated a remarkable antibacterial activity against several bacterial isolates, were cis-calamenene (22.7%) and leptospermone (19.2%), as already reported in a previous study [38].…”
Section: Essential Oil Compositionsupporting
confidence: 80%
“…Furanoeudesma-1,3-diene, a particular compound with antimicrobial activity [37], was also present in high percentage in Commiphora molmol EO (33.7%). The compounds most represented in Leptospermum scoparium EO, which have demonstrated a remarkable antibacterial activity against several bacterial isolates, were cis-calamenene (22.7%) and leptospermone (19.2%), as already reported in a previous study [38].…”
Section: Essential Oil Compositionsupporting
confidence: 80%
“…On the other hand, α‐pinene was also present in all the tested EOs, also in those with a moderate or low activity. This occurrence confirms the hypothesis that this compound could react in with other ones in a synergistic effect 35,36 . The review of Bassolé 37 reported a synergic effect between α‐pinene and limonene.…”
Section: Resultssupporting
confidence: 81%
“…This occurrence confirms the hypothesis that this compound could react in with other ones in a synergistic effect. 35,36 The review of Bassolé 37 and S aureus. 39 The Indian Cymbopogon martini studied before 40 revealed the highest sensitivity of its EO against S epidermis and E coli, due to its richness in p-menthadienols (more than 57% of identified fraction whose 14.4% was represented by p-mentha-1, 7 8-dien-2-ol).…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…The main compounds in Sm were carvacrol (45.4%), p-cymene (10.3%) and thymol (7.0%), and the most representative in Ls were cis-calamenene (21.4%), leptospermone (18.3%) and flavesone (6.9%). As regards the compounds' concentration in the Sm and Ls Eos, it is interesting to note that Ls and Sm compositions were slightly different from what was reported previously [29]. These little differences may be due to the degradation of components during the refrigerated storage.…”
Section: Resultsmentioning
confidence: 51%